1997
DOI: 10.1034/j.1399-3054.1997.1010404.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytokinin content in plant cells

Abstract: Cytokinin levels in plant cells are dependent on cytokinin biosynthesis and/or uptake from extracellular sources, metabolic interconversions, inactivation and degradation. Cytokinin conversion to compounds differing in polarity seems to be decisive for their entrapment within the cell and intracellular compartmentation, which affects their metabolic stability. Increase in cytokinin levels, resulting either from their uptake or intracellular biosynthesis, may promote further autoinductive accumulation of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Numbers represent inferred enzymes as follows: 1. adenosine kinase (EC 2.7.1.20); 2. purine nucleotide phosphorylase (EC 2.4.2.1); 3. adenine phophoribosyltransferase (EC 2.4.2.1). The remaining arrows demonstrate alternative conversions that can occur via specific enzymes in other CK producing organisms, such as Arabidopsis . Bolded text refers to the CK forms that were dominant and the proposed enzyme activity that we observed in this study.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Numbers represent inferred enzymes as follows: 1. adenosine kinase (EC 2.7.1.20); 2. purine nucleotide phosphorylase (EC 2.4.2.1); 3. adenine phophoribosyltransferase (EC 2.4.2.1). The remaining arrows demonstrate alternative conversions that can occur via specific enzymes in other CK producing organisms, such as Arabidopsis . Bolded text refers to the CK forms that were dominant and the proposed enzyme activity that we observed in this study.…”
Section: Resultsmentioning
confidence: 90%
“…Of the naturally occurring CKs in plants, the isoprenoid‐type CKs, N 6 ‐isopentenyladenine (iP), trans ‐zeatin ( t Z), cis ‐zeatin ( c Z), and dihydrozeatin (DZ), are the most common . Much less has been documented about aromatic‐type CKs, such as N 6 ‐benzyladenine (BA) . The majority of naturally occurring CKs exist in distinctive structural derivatives or forms such as: free bases (FBs), ribosides (Rs), and nucleotides, or conjugates with glucose, xylose, or amino acid residues .…”
Section: Introductionmentioning
confidence: 99%
“…The high proportion of iP7G and iPRMP compared to iP and iPR in Tc‐treated cells probably resulted from their partial or complete resistance to degradation by CKX. It has been suggested that the induction of CKX activity by both exogenous and endogenous cytokinins contribute to the re‐establishment and maintenance of cytokinin homeostasis in plant cells (Kamínek et al. 1997, Zažímalová et al.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the impressive progress made in CKX research, little is known about the regulation of CKX activity in plant tissues and cells. It is apparent that the CKX in plant cells is subjected to multiple regulatory mechanisms, most of them depending directly on the concentration and/or compartmentation of cytokinins in the cell (reviewed in Armstrong 1994, Jones and Schreiber 1997, Kamínek et al. 1997).…”
Section: Introductionmentioning
confidence: 99%
“…3 The active cytokinin pool could be regulated via modulation of biosynthesis, transport, metabolic interconversion or catabolism. 4 Cytokinin metabolism has been investigated in a range of species. 5,6 N-Glucosyl conjugation and oxidative cleavage of the isoprenoid side-chain have been identified as the major mechanisms of inactivation.…”
Section: Introductionmentioning
confidence: 99%